The Influence of Social Media and Product Quality on Purchase Intention on MSME Mitra Mandiri Brebes - Dumadi Dumadi; Slamet Bambang Riono (Harmony Management: International Journal of Management Science and Business, 2025)
The impact of the Covid-19 pandemic was experienced by business actors, especially MSME business actors and had a huge impact on business actors who had just started a business. The Covid-19 pandemic that hit the world has made many changes, including the changing behavior of consumers. MSME actors must be able to adapt to existing conditions. Consumers prefer to make purchases onlineonline according to their circumstances and needs during a pandemic, but this right is also inseparable with regard to the quality of the product to be purchased, whether it meets their needs or not. The research objectives were to find out and analyze the influence of: social media on buying interest, product quality on buying interest, and social media and product quality on buying interest in UMKM Mitra Mandiri Brebes. The research population referred toFriends of the Umkm Mitra Mandiri account as of October 15, 2023 totaling 201 friends. Sampling using the Slovin formula with techniquesincidental as many as 67 respondents. The data uses primary data from the answers to the questionnaire. Hypothesis testing uses SPSS. The theoretical basis used is social media, product quality, and buying interest. The results showed social media partially has a significant effect on purchase intention, product quality partially has a significant effect on purchase intention, and social media and product quality simultaneously influence purchase intention